A Study on the driving and hindering factors for renewable energy development - JEONG, Jungi (KDI School, 2024)
We are currently living in an era of climate change crisis. The most significant portion contributing to greenhouse gas emissions, identified as the cause of climate change, lies within the energy sector. Much of humanity's energy consumption has relied on fossil fuels. Transitioning from fossil fuels to renewable energy is a direction the world must undoubtedly take. As part of these efforts, installations of renewable energy, primarily solar energy, have steadily increased. However, the recent conditions for renewable energy supply are unfavorable. While the installed capacity of renewable energy in Korea has been steadily increasing, its proportion in the overall power mix remains low. Particularly, the annual supply of solar energy has decreased over the past three years. Various conditions must be addressed for the proactive development of renewable energy. Achieving this goal requires meeting all review factors, including resident acceptance issues, power grid concerns, licensing issues, profitability concerns such as generation capacity and revenue, and others. In this study, necessary review elements for the expansion of renewable energy were categorized into four areas and detailed, while licensing matters and project implementation procedures were analyzed. Based on this, realistic challenges faced in the field were summarized through in-depth interviews with practitioners involved in renewable energy projects. Consequently, procedural improvements necessary to facilitate project execution and methods for community involvement were presented. Various measures to promote the supply of renewable energy will contribute to addressing the climate change crisis.
Thesis(Master) -- KDI School: Master of Public Management, 2024
Keywords: Renewable energy sources; Energy conservation